The Influence of Compost and Biochar on the Physico-Chemical Properties of Soil and the Growth of Tomatoes in Sub-Optimal Land - Endriani, Endriani; Sa’ad, Asmadi; Listyarini, Diah (JOURNAL OF TROPICAL SOILS, 2025)
This study seeks to evaluate the effectiveness of coconut shell biochar (CB)  and/or Leucaena compost (LC) as ameliorants in improving soil chemical and physical properties, as well as enhancing tomato yields. The goal is to identify the most effective combination of ameliorant formulations that can improve land quality and increase yield of tomato. The study was carried out over a 10-month period, spanning from March 2024 to December 2024. The research method used a Group Random Design, the treatments studied were: A0: no ameliorant + inorganic fertilizer as recommended;   A1 :  CB 15 Mg ha-1;   A2 :  LC 15 Mg ha-1;   A3 : LC 5 Mg ha-1 + CB  10 Mg ha-1;   A4 : LC 10 Mg ha-1 + CB 5 Mg ha-1. All treatments were repeated 5 times.  The data obtained from this study were subjected to statistical analysis and further evaluated using the Duncan’s New Multiple Range Test (DNMRT). The findings reveal that applying coconut shell biochar and Leucaena compost, whether individually or in combination, markedly enhances the physical properties of the soil. These improvements include reduced bulk density (BD), increased soil organic matter SOM), total porosity (TP), and hydraulic conductivity (HC), as well as better pore distribution and water retention. Furthermore, these treatments resulted in an increase in both the tomato weight per plant and the fresh tomato weight per plot. The most effective combination for maximizing tomato yield was determined to be 10 Mg ha-1 of LC combined with 5 Mg ha-1 of CB.